Dakwah Contributions - awis karni (Al-Hikmah: Jurnal Dakwah dan Ilmu Komunikasi, 2006)
Civil Society is a symbol where all citizens can control reality. It presents in many parties, groups, organizations, institutions and many others. The people as existence express the presentations of other institutions beside govermment in order to get balance. This article discuses contribution of Dakwah in making civil society.